RUSSIA IN MODERN EURASIA: THE VISION OF A RUSSIAN GEOGRAPHER - Druzhinin, Alexander G. (Quaestiones Geographicae, 2016)
It is demonstrated that ‘Eurasianism’ as an interdisciplinary scientific doctrine and an object-focused area of geographical social science is at its root, generally complementary to the methodology of Russian (Soviet) socio-economic (human) geography, and corresponds to its research tradition. The geo-economic, geopolitical and geo-cultural transformation of the post-Soviet ‘Eurasian space’ is analysed. The geo-concept of a multipolar ‘Mega-Eurasia’is proposed and justified. It is emphasised that the effective participation of Russia as one of the dominants of the Eurasian space is associated with the non-admission of an extremely undesirable, harmful scenario for Russia as well as of its possible marginalisation and limitation to the flimsy framework of the ‘Russian world’. A hypothetically possible commitment to only one of the existing global ‘power centres’ is also considered to be a losing one.